Efektivitas Penghimpunan Dana Zakat, Infak, dan Shadaqah Pada Program Ramadhan 1440 H oleh Inisiatif Zakat Indonesia (IZI) Cabang Padang - Revi Hayati; Afra Nadilla; M.S Almuajddedi (Jurnal Ilmiah Ekonomi Islam, 2021)
The purpose of this study was to examine the effectiveness of collecting zakat, infaq and shadaqah funds in the Ramadhan 1440 H program. The Indonesian Zakat Initiative (IZI) Padang Branch is one of the amil zakat institutions in West Sumatra. One of the activities of IZI Padang is to collect zakat funds in the month of Ramadan in 1440 H under the name "Ramadan Program" where the program has not been implemented effectively. This research is a field research using qualitative descriptive analysis. Sources of data in this study were obtained through observation, interviews, and documentation of sources relevant to the research problem. The results of this study are 1) IZI Padang's strategies in carrying out the "Ramadan Program" activities are a) opening outlets in various places, b) cellphoneing, and c) funrising. 2) Volunteer motivation in carrying out the "Ramadan Program" activity comes from a) the support from superiors and work partners, b) training, c) personal capabilities from volunteers, d) compensation, and e) responses from different communities. different.